2018
DOI: 10.2147/tcrm.s171970
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hip fracture in patients on dialysis or kidney transplant: a meta-analysis of 14 cohort studies

Abstract: PurposeWe aimed to conduct a meta-analysis of published cohort studies to evaluate the risk of hip fracture in patients undergoing dialysis or kidney transplantation (KT).MethodsWe identified relevant studies by searching PubMed, EMBASE and Google Scholar databases from their inception to December 31, 2017. Cohort studies evaluating risk of hip fractures in patients undergoing dialysis or KT were considered included. The methodological quality of the cohort studies was assessed using the modified Newcastle-Ott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…7 reported that the overall fracture IR was 62.8 per 1000 PY in all ESKD patients, 99.2 per 1000 PY for those exposed to HD, 57.6 per 1,000 PY for those treated with PD, and 37.6 per 1000 PY for those undergoing KT. As for the hip fractures, however, our data showed an IR of 8.7 per 1000 PY for all patients with ESKD, 9.7 per 1000 PY for patients treated with HD, which was comparable to data reported in previous studies 2,8 . Our data are consistent with other reports, showing a higher fracture IR in ESKD patients than in the general population 1,2,9,10 .…”
Section: Discussionsupporting
confidence: 91%
“…7 reported that the overall fracture IR was 62.8 per 1000 PY in all ESKD patients, 99.2 per 1000 PY for those exposed to HD, 57.6 per 1,000 PY for those treated with PD, and 37.6 per 1000 PY for those undergoing KT. As for the hip fractures, however, our data showed an IR of 8.7 per 1000 PY for all patients with ESKD, 9.7 per 1000 PY for patients treated with HD, which was comparable to data reported in previous studies 2,8 . Our data are consistent with other reports, showing a higher fracture IR in ESKD patients than in the general population 1,2,9,10 .…”
Section: Discussionsupporting
confidence: 91%
“… 29 The increased risk of fracture has also been observed among CKD patients after kidney transplantation. 32 , 33 Over the first 3 years following transplantation, the risk of a hip fracture is 34% higher than in dialysis patients, and over the first 5 years post‐transplant one‐fourth will have a fracture. 33 A recent meta‐analysis has disclosed an overall fracture incidence rate of 8.95 per 1,000 person‐years among dialysis patients and kidney transplant recipients (KTR).…”
Section: Vascular and Bone Abnormalities In Ckdmentioning
confidence: 99%
“… 33 A recent meta‐analysis has disclosed an overall fracture incidence rate of 8.95 per 1,000 person‐years among dialysis patients and kidney transplant recipients (KTR). 32 …”
Section: Vascular and Bone Abnormalities In Ckdmentioning
confidence: 99%
“…(1,2) Hemodialysis patients are known to have a higher risk of hip fracture than the general population. (3,4) However, it is less clear whether individuals with mild to moderate chronic kidney disease (CKD) are at increased risk for hip fracture. Ensrud and colleagues found that elderly women with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73m 2 had a higher risk of hip fracture than women with normal kidney function.…”
Section: Introductionmentioning
confidence: 99%